Electoral Cycles in Macroeconomic Forecasts - Davide Cipullo; André Reslow (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper documents the existence of Political Forecast Cycles. In a theoretical model of political selection, we show that governments release overly optimistic GDP growth forecasts ahead of elections to increase the reelection probability. The bias arises from lack of commitment if voters are rational and from manipulation of voters' beliefs if they do not expect the incumbent to be biased. Using high-frequency forecaster-level data from the United States, the United Kingdom, and Sweden, we document that governments overestimate short-term GDP growth by 10 to 13 percent during campaign periods.
Keywords: D72; D82; E37; H68; 330; electoral cycles; political selection; voting; macroeconomic forecasting